Abdurrahman Ali El-Hajji. Al-Tārīkh al-Andalusī: Min al-Fatḥ al-Islāmī ḥattā Suqūṭ Gharnāṭa (The Andalusian History: from the Beginning until the End of Granada( )). A.H. 92-897/A.D. 711-1492. Damascus: Dār al-Qalam, 1981, 605 pp. - SAIFI, Mounir (Al-Andalus Magreb, 2022)
In his Al-Tārīkh al-Andalusī, based on a number of Muslim historiographic sources, El-Hajji relates, in a chronological order, the different military and political events and social changes al-Andalus went through from the Muslim conquest in 711 to the fall of Granada, the last Muslim stronghold in Iberia, in 1492. Each of the eight chapters of the book is dedicated to a particular era or series of major events in the history of al-Andalus.